Inductive transfer applied to modeling river discharge in Nova Scotia - Silver, Daniel; Spooner, Ian; Gaudette, Lisa (Atlantic Geology)

(untitled) (Atlantic Geoscience Society, 2009)
ABSTRACT Effective watershed management requires accurate modeling of river discharge. Many years of data collection are often required to capture variations in seasonal trends and produce accurate predictive and descriptive models. In this study artificial neural networks that employ inductive transfer are used to develop models that predict the discharge (flow rate) of streams in Nova Scotia from weather data. The models use two days of weather data to predict the discharge for the following day. The objective is to show that transfer of knowledge from previously learned models for streams can be used to reduce the time and cost associated with collecting large amounts of data for modeling the discharge of a nearby river. Results show that models developed using only 180 days of training data with transfer from related streams perform as well on independent test data as models constructed using five years of training data and no transfer. The results also show that a considerable variance in stream discharge and stream morphology can be accommodated and that the induced models may be acceptable for management of the resource when little data are available. There is scope for improving the method of transfer by taking into consideration the degree of relatedness between the streams, watersheds, and their associated climate conditions.